Predictors of early ART initiation among HIV+ infants in Kenya: A retrospective review of HITSystem data from 2013-2017. - Wexler, Catherine (Matern Child Health J, 2020)
OBJECTIVE: Early initiation of antiretroviral therapy (ART, before 12 weeks of age) among infants living with HIV reduces infant mortality and slows disease progression. However, inefficiencies in early infant diagnosis processes prevents timely ART initiation among infants living with HIV in Kenya. This study assesses predictors of early ART initiation among infants living with HIV in Kenya. DESIGN: We retrospectively reviewed data from 96 infants living with HIV born between January 2013 and June 2017 at 6 Kenyan government hospitals. METHODS: The primary outcome was infant receipt of ART by 12 weeks of age. We assessed bivariable and multivariable predictors of ART initiation by 12 weeks of age. RESULTS: Among 96 infants living with HIV, 82 (85.4%) infants initiated ART at a median infant age of 17.1 weeks. Of the 82 infants who started ART, only 17 (20.7%) initiated ART by 12 weeks of age. In multivariable logistic regression analyses, testing per national guidelines (< 7 weeks of age) (aOR 40.14 [3.96-406.97], p=0.002), shorter turnaround time for result notification (≤ 4 weeks) (aOR 11.30 [2.02-63.34], p=0.006), and ART initiation within 3 days of mother notification (aOR 7.32 [1.41-38.03], p=0.006) were significantly associated with ART initiation by 12 weeks of age. CONCLUSION: Current implementation of early infant diagnosis services in Kenyan only achieves targets for early ART initiation in one-fifth of infants with HIV. Strengthening services to support earlier infant testing and streamlined processes for early infant diagnosis may increase the proportion of infants who receive timely ART.